Functionally graded additive manufacturing to achieve functionality specifications of osteochondral scaffolds - Monzón, M. (2018)
Osteoarthritis (OA) is a degenerative joint disease, characterized by cartilage loss and changes in bone at the interface of a joint resulting in pain, stiffness and reduced mobility. OA is one of the most prevalent chronic conditions as identified in Bone and Joint Decade. According to the World Health Organization, 40% of people over the age of 70 have OA. This joint disease affects around 0.4 billion people with patients in Europe accounting for up to 30%. The figure is set to increase with the ageing problem. Current non-surgical treatments for OA involve non-steroidal anti-inflammatory drug administration. Surgical treatments include osteotomy, abrasion arthroplasty, micro-fracture and autologous chondrocyte implantation (ACI). This is a two-stage surgical procedure with the associate costs and infection being the main concern. For small osteochondral defects, micro-fracture (MF) marrow stimulation and for large cartilaginous defects the autologous chondrocyte implantation are considered as necessary treatments. However, MF produces fibrocartilage not native hyaline cartilage. For defects that have progressed to a stage that affects the subchondral bone, other treatments are no longer effective and joint replacement operation is the only alternative. The demand for innovative therapeutic alternatives for complete healing of OA is significant. The treatment of cartilage and osteochondral (OC) defects remains a challenge since treatments so far have failed to achieve complete restoration of the properties of joint cartilage. Many new technologies, such as osteochondral tissue engineering, have been studied and applied to repair osteochondral defects. Commercially available osteochondral scaffolds have been used in patients with OC defects. However, no products have so far demonstrated to provide biomechanical properties suitable to promote the durable regeneration of large OC defects [1]. The main issue with these commercially available OC scaffolds is poor cartilage fill associated with fibrocartilage formation. The aim of this paper is to define the functionality and performance which would be required for intended clinical applications in the treatment of osteoarthritis and also to show that the capabilities of 3D bioprinting and functionally graded additive manufacturing scaffolds are suitable to meet most of these requirements.